Angle Trisection: 1.What is Angle Trisection? 2.How To Do Angle Trisection? 3.Why Do Angle Trisection? - Husyan Pour Shad, Mehryar (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
We seek to increase the development of science, but there are several fundamental questions about what is. Without solving the question is a false reflection of the history of science and the beginning of cognition. We know that their investigation and resolution, with the exception of rooting and knowledge of morphophonemic, do not come. Research on certain natural or pure mathematical phenomena is an example of my fundamental research that will lead to the definition of general principles and scientific theories.